Entrepreneurial cultural affinity spaces (ecas): Design of inclusive local learning ecosystems for social change, innovation and entrepreneurship - Savva, Stefania; Souleles, Nicos; Ferreira, Ana Margarida (My University, 2020)
The ECAS framework seeks to transform social design theory and practice through an emergent instructional paradigm of heritage-led, local learning ecosystem approaches, to leverage on diverse assets of people in community settings. This includes the cultural, social, sexual and religious diversity of locals. Such reconfiguration of design for social change, and our collective mindset, will create the conditions for more dynamic and powerful collaborations that stimulate and enable social innovation, entrepreneurship, and inclusion. The conceptual backdrop draws on the concepts of affinity spaces and embodied learning, incorporated into local learning ecosystem ideas that support viable, integrated and participative urban regeneration. This paper addresses the theoretical backdrop of how such ecosystems can be co-designed, implemented and evaluated, to include disadvantaged and underrepresented groups, such as minorities, women, migrants, refugees and asylum seekers, to empower them as lifelong learners and change-makers. We introduce the ECAS framework and how it can present an inclusive and open instructional paradigm that improves design for social change, innovation and entrepreneurship in practice through the framework, conditions, and support mechanisms developed.
Keywords: Circular economy; Embodiment; Entrepreneurship; Local learning ecosystems; Social design; Social innovation; Urban regeneration